Snakes and Ladders: The experience of being referred to and seen by Child and Adolescent Mental Health Services - Kristina L. Newman; Kapil Sayal; Colleen Ewart; Alexandra Lang; Anupam Bhardwaj; Bernadka Dubicka; Tamsin Marshall; Louise Thomson (Elsevier, 2024)
Background: Referral processes in Child and Adolescent Mental Health Services (CAMHS) have been reported as stressful and inadequate by young people and parents/carers, who struggle during waiting periods for the referral outcome decision. The Covid19 pandemic was an unprecedented time of distress for young people, parents/carers, and healthcare staff, with increased mental health challenges and stretched staff having to adapt modes of care, thus exacerbating difficulties for CAMHS. Aim: This qualitative study aimed to capture the unique lived experiences of young people, parents/carers, and CAMHS staff during the referral process in the peak of the Covid19 pandemic. Methods: As part of the STADIA trial, between 2020 and 2022, 109 semi-structured interviews across 8 NHS sites were conducted with young people (aged 16-17), parents/carers, and NHS staff including clinicians, commissioners, managers, and researchers embedded in clinical services. Interviews were analysed using thematic analysis. Results: Three themes were elicited to express young people, staff, and parents/carer experiences of the referral process, CAMHS, and the impact of Covid19: 1) referral as a starting point; 2) changes to methods of appointment delivery and their effect on CAMHS experience; and 3) experiences and evaluation of services. Conclusion: Although CAMHS was seen as the pinnacle of mental health support, there was dissatisfaction with waiting times, limited communication, unclear referral processes, and limited clinical capacity and resources for young people, parent/carers, and staff. Covid19 forced CAMHS into adapting to a hybrid model of care, increasing accessibility for young people, parents/carers and staff and highlighting areas for improvement. Secure and consistent support and increases in staff resources are essential to address challenges with CAMHS delivery and improve the experiences of young people, parent/carers, and staff.